2012
DOI: 10.1111/j.1399-3054.2012.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Root‐derived auxin contributes to the phosphorus‐deficiency‐induced cluster‐root formation in white lupin (Lupinus albus)

Abstract: Formation of cluster roots is a typical morphological response to phosphorus (P) deficiency in white lupin (Lupinus albus), but its physiological and molecular mechanisms are still unclear. We investigated the role of auxin in the initiation of cluster roots by distinguishing the sources of auxin, measuring the longitudinal distribution patterns of free indole-3-acetic acid (IAA) along the root and the related gene expressions responsible for polar auxin transport (PAT) in different developmental stages of clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
5
20
0
2
Order By: Relevance
“…It has been suggested that TIBA acts as a competitive inhibitor of auxin transport [52]. Our results showing TIBA significantly inhibiting LR and CR formation ( Figures 3D-F and 4) are consistent with previous observations that TIBA can interfere with NAA activity [15,35,36]. Taken together, these results confirm that auxin plays an essential role in regulating root development of white lupin.…”
Section: Root Morphological Traits As Affected By Auxin In Response Tsupporting
confidence: 92%
See 4 more Smart Citations
“…It has been suggested that TIBA acts as a competitive inhibitor of auxin transport [52]. Our results showing TIBA significantly inhibiting LR and CR formation ( Figures 3D-F and 4) are consistent with previous observations that TIBA can interfere with NAA activity [15,35,36]. Taken together, these results confirm that auxin plays an essential role in regulating root development of white lupin.…”
Section: Root Morphological Traits As Affected By Auxin In Response Tsupporting
confidence: 92%
“…In rice, exogenous auxin can amplify P starvation signaling [38], and a cross-talk exists between auxin and P starvation [39]. Application of exogenous auxin increases LR formation in Arabidopsis and CR proliferation in white lupin, whereas auxin antagonists reduce these effects [35,36,50,51]. These findings support the view that most effects of P deficiency on root morphological responses depend primarily on auxin signaling.…”
Section: Root Morphological Traits As Affected By Auxin In Response Tsupporting
confidence: 60%
See 3 more Smart Citations